How Constructive Journalism Helps the Small and Medium Enterprises - Lulu Awanila; Nabila Zummrah Rubbah; Nurul Amalia Rizki (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2021)
MSMEs have an important role to support the economy in Indonesia and are the driving force for the growth of national economic activity. On the other hand, the role of MSMEs is also very important because they are able to develop trade, reduce poverty and create jobs. But unfortunately not many MSMEs are able to introduce their products to the wider community. The purpose of this study is to analyze the role of journalism needed to help entrepreneurs channel their business results. To analyze, we used qualitative research methods by directly interviewing several sources in the field of journalism and entrepreneurs, in this case MSMEs. The research instrument produced by this method is the result of the interview. The results of this study have proven that journalism can help entrepreneurs in this case what is meant here is MSMEs in developing their businesses and helping MSMEs in achieving their goals.